Effects of Patisiran, an RNA Interference Therapeutic, on Cardiac Parameters in Patients With Hereditary Transthyretin-Mediated Amyloidosis: Analysis of the APOLLO Study. Issue 4 (22nd January 2019) - Solomon, Scott D.; Adams, David; Kristen, Arnt; Grogan, Martha; González-Duarte, Alejandra; Maurer, Mathew S.; Merlini, Giampaolo; Damy, Thibaud; Slama, Michel S.; Brannagan, Thomas H.; Dispenzieri, Angela; Berk, John L.; et al.
Abstract : Background: Hereditary transthyretin-mediated (hATTR) amyloidosis is a rapidly progressive, multisystem disease that presents with cardiomyopathy or polyneuropathy. The APOLLO study assessed the efficacy and tolerability of patisiran in patients with hATTR amyloidosis. The effects of patisiran on cardiac structure and function in a prespecified subpopulation of patients with evidence of cardiac amyloid involvement at baseline were assessed. Methods: APOLLO was an international, randomized, double-blind, placebo-controlled phase 3 trial in patients with hATTR amyloidosis. Patients were randomized 2:1 to receive 0.3 mg/kg patisiran or placebo via intravenous infusion once every 3 weeks for 18 months. The prespecified cardiac subpopulation comprised patients with a baseline left ventricular wall thickness ≥13 mm and no history of hypertension or aortic valve disease. Prespecified exploratory cardiac end points included mean left ventricular wall thickness, global longitudinal strain, and N -terminal prohormone of brain natriuretic peptide. Cardiac parameters in the overall APOLLO patient population were also evaluated. A composite end point of cardiac hospitalizations and all-cause mortality was assessed in a post hoc analysis. Results: In the cardiac subpopulation (n=126; 56% of total population), patisiran reduced mean left ventricular wall thickness (least-squares mean difference ± SEM: –0.9±0.4 mm, P =0.017), interventricular septal wall thickness, posterior wall thickness, and relative wall thickness at month 18 compared with placebo. Patisiran also led to increased end-diastolic volume (8.3±3.9 mL, P =0.036), decreased global longitudinal strain (–1.4±0.6%, P =0.015), and increased cardiac output (0.38±0.19 L/min, P =0.044) compared with placebo at month 18. Patisiran lowered N -terminal prohormone of brain natriuretic peptide at 9 and 18 months (at 18 months, ratio of fold-change patisiran/placebo 0.45, P <0.001). A consistent effect on N -terminal prohormone of brain natriuretic peptide at 18 months was observed in the overall APOLLO patient population (n=225). Median follow-up duration was 18.7 months. The exposure-adjusted rates of cardiac hospitalizations and all-cause death were 18.7 and 10.1 per 100 patient-years in the placebo and patisiran groups, respectively (Andersen–Gill hazard ratio, 0.54; 95% CI, 0.28–1.01). Conclusions: Patisiran decreased mean left ventricular wall thickness, global longitudinal strain, N -terminal prohormone of brain natriuretic peptide, and adverse cardiac outcomes compared with placebo at month 18, suggesting that patisiran may halt or reverse the progression of the cardiac manifestations of hATTR amyloidosis. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01960348. Abstract : Supplemental Digital Content is available in the text.